Zionism and Cosmopolitanism Franz Oppenheimer and the Dream of a Jewish Future in Germany and Palestine - Peretz, Dekel (Europäisch-jüdische Studien - Beiträge, 2022)
Franz Oppenheimer (1864-1943) was a prominent German sociologist, economist and Zionist activist. As a co-founder of academic sociology in Germany, Oppenheimer vehemently opposed the influence of antisemitism on the nascent field. He and other German Zionists believed Zionism could strengthen German-Jewish identity. They presented Zionism as an extension of German patriotism by positioning Zionist aspirations within a German colonial narrative.